Impacto de la inestabilidad tecnológica en la institución educativa “Emigdio Esparza Moreno” de la ciudad de Babahoyo - Salazar Bustamante, Marlon José (2021)
Technological instability is present in most of the marginal urban and rural sectors of Ecuador, the Los Ríos province has an extensive population in the rural area and the city of Babahoyo in the same way, the Emigdio Esparza Moreno Educational Unit is an Institution with a It has a long history and is considered by the population as one of the largest and with renowned prestige that welcomes students from various sectors including students from marginal urban and rural areas. As the situation of the Institution is manifested in relation to the residence of the students, the new form of teaching that was applied for reasons of confinement, has the internet as its main tool and also required that all its members have it and also possess technological equipment with certain characteristics to be able to maintain good connectivity and be able to listen to their classes, the objective of this research work aims to analyze the impact of technological instability in the educational institution "Emigdio Esparza Moreno" in the city of Babahoyo For the development of this case study, a qualitative, descriptive approach was used, and for the collection of information, the poll technique was applied with the help of the questionnaire as an instrument